HUBUNGAN PENGETAHUAN, SIKAP DAN MOTIVASI IBU DENGAN PERILAKU PENCEGAHAN KEJANG DEMAM BERULANG PADA BALITA USIA 1- 5 TAHUN DI RSUD RADEN MATTAHER JAMBI - Untung Tarunaji; Fithriyani Fithriyani (Jurnal Akademika Baiturrahim Jambi, 2018)
ABSTRACTA febrile seizure is a seizure that occurs when an infant or child has a fever without central nervous system infection that occurs at temperatures over 380 C. a febrile seizure is seizure type most often encountered in childhood. This study aimed to determine the correlation of knowledge, attitude and mother’s motivation with behavior of febrile seizures prevention in toddlers’ age 1-5 years in the child’s room RSUD Raden Mattaher Jambi year 2017. This is a quantitative research by using cross sectional design, it used Accidental Sampling by using questionnaire instrument. This study analyzed as univariate and bivariate by using chi-square test with significant levels 95% (<0.05).The findings indicated that, 35 respondents as many as 19 (54.3%) have low knowledge, less good attitude as many as 20 (57.1%), less good motivation as many as 18 (51.4%) and less good prevention behavior 18 (51.4%). The result of chi-square test indicated that there is the correlation of knowledge, attitude and mother’s motivation with behavior of febrile seizures prevention in toddlers age 1-5 years in the child’s room RSUD Raden Mattaher Jambi year 2017 with p-value < 0.05 while the motivation, there is no correlation with behavior of febrile seizures prevention in toddlers age 1-5 years in the child’s room RSUD Raden Mattaher Jambi year 2017 p-value > 0.05. It is expected to RSUD Raden Mattaher Jambi is not only providing treatment but also providing health education periodically to increase of knowledge, attitude and mother’s motivation so the febrile seizures do not reoccur.